Boże zwycięstwo (ενθεοσ νικη) – „ideologia tryumfu” w "Historii kościelnej" Euzebiusza z Cezarei - Bralewski, Sławomir (Vox Patrum, 2015)
“Ideology of victory” occupied a very important place in Ecclesiastical History by Eusebius of Caesarea. The victory which he described had a sacred dimension. It was God’s triumph in a war which mankind declared on God himself. Its turning point was the appearance of the Word of God, Wisdom, Jesus Christ, who taught people how to worship God the Father and who was given the power, the eternal reign of the everlasting kingdom. Together with his advent, according to Eusebius, a new Christian people came into being. Since it adopted the lifestyle and customs based on piety originating from the beginnings of mankind, it was not, in fact, a new nation. Christians fought a war against evil spirits, which were hostile to people and which hated God, my means of pure love. Christ, as God’s commander in chief, the Lord and the King, led this battle. Eusebius stated that He armed his army with piety and defeated the enemies completely. Victories achieved by Christians over the enemies of God, inspired by the evil spirit and dominated by hubris, had several dimensions: sacral-military, martyr’s and doctrinal. The first one corresponded to the Roman tradition and was connected with the choice of the divine patron, to whose power military victories were attributed. Emperor Constantine played a special role in it, as, on the one hand, he chose the Christian God to be his ally and, on the other hand, was himself chosen by God and became a God’s tool. Having defeated God’s enemies, the Emperor put an end to the war between God and mankind and eliminated all the hatred to Him from the world. From the perspective of martyrdom, Christians seemingly suffered a defeat, while their prosecutors saw the triumph of their own gods in the suffering and death of Christians. In fact, martyrs, under the sign of Christ, the great and undefeated athlete, triumphed giving their life for God, which was God’s victory. As a reward for their sacrifice they received the wonderful wreath of immortality. In the third, doctrinal dimension the truth preached by Christians triumphed over false teachings and predominated over them by virtue of their holiness and wisdom and divine and philosophical principles, on which it was based.